A qualitative exploration of stakeholders’ perspectives on the experiences, challenges, and needs of persons with serious mental illness as they consider finding a partner or becoming parent - Dubreucq, Marine; Lysaker, Paul H.; Dubreucq, Julien (Frontiers in Psychiatry, 2023)
While many persons with serious mental illness (SMI) consider intimate relationships and becoming parent as central parts of their lives deeply affecting wellbeing and recovery, others anticipate facing multiple challenges in these life domains. Objective: This qualitative study sought to explore the views, perspectives, preferences and expectations of various stakeholders (i.e. persons with SMI and mental health providers (MHPs)) on service provision to support people with SMI as they consider finding a partner or becoming parent. Design: The present study used a qualitative design, using focus groups Methods: Five focus groups were conducted between March and December 2020for a total number of 22 participants (2 groups composed of persons with SMI (n=9) and 3 groups composed of MHPs (n=13) recruited from a center for psychiatric rehabilitation and a community mental health center) in France . Results: Participants reported some challenges related to intimate relationships, stigma/self-stigma, disclosure and decision-making about start a family but also many resources. Their expectations included: i) psychoeducation about decision-making about finding a partner and starting a family; ii) support in making empowered decisions about finding a partner, starting a family or disclosure to a prospective partner or their child; iii) peer-support interventions; iv) enhancing coping strategies, v) integrated service provision including home treatment interventions, training to recovery-oriented practices and access to dedicated resources for providers. Conclusions : In short, intimate relationships and desire to start a family for persons with SMI should be more considered in psychiatric rehabilitation and additional support and interventions should therefore be provided.